Codetermination in Germany: A beginner's guide - Lionel Fulton (Hans-Böckler-Stiftung, Institut für Mitbestimmung und Unternehmensführung (I.M.U.), 2020)
This guide is intended to help people unfamiliar with the German system of labour relations to understand one of its key aspects, the system of employee involvement known as 'codetermination' ('Mitbestimmung' in German). Codetermination is governed by a series of rules set out in legislation and provides employee representatives with clear rights to act in ways that benefit the employees who elected them. Codetermination also requires employee representatives to consider the interests of the business where they work and there is evidence that codetermination brings benefits to the companies in which it is exercised. Codetermination affects decisions at all levels and plays a role in German companies and those who work in them, making it an important element not just of German industrial relations, but also of the German economy and German society. Anyone who wishes to understand the German economy and society better would be well advised also to take time to learn a little about codetermination. The guide is intended for non-Germans encountering the codetermination for the first time. Whether they are managers or investors, trade union officials or elected employee representatives, they are likely to find initially that parts of the system seem unfamiliar and perhaps uniquely German. But on closer examination, it is clear that codetermination has many features in common with other systems of employee involvement elsewhere in Europe. The rules and the structures may differ but the concerns and needs are the same.
urn:nbn:de:101:1-2020071011152710894338
Keywords: 650; Codetermination; German system of labour; employee representatives; German companies; industrial relations; economy; social system; trade union